Increased mitochondrial Ca2+ contributes to health decline with age and Duchene muscular dystrophy in C. elegans. Issue 4 (19th March 2023) - Higashitani, Atsushi; Teranishi, Mika; Nakagawa, Yui; Itoh, Yukou; Sudevan, Surabhi; Szewczyk, Nathaniel J.; Kubota, Yukihiko; Abe, Takaaki; Kobayashi, Takeshi
Abstract: Sarcopenia is a geriatric syndrome characterized by an age‐related decline in skeletal muscle mass and strength. Here, we show that suppression of mitochondrial calcium uniporter (MCU)‐mediated Ca 2+ influx into mitochondria in the body wall muscles of the nematode Caenorhabditis elegans improved the sarcopenic phenotypes, blunting movement and mitochondrial structural and functional decline with age. We found that normally aged muscle cells exhibited elevated resting mitochondrial Ca 2+ levels and increased mitophagy to eliminate damaged mitochondria. Similar to aging muscle, we found that suppressing MCU function in muscular dystrophy improved movement via reducing elevated resting mitochondrial Ca 2+ levels. Taken together, our results reveal that elevated resting mitochondrial Ca 2+ levels contribute to muscle decline with age and muscular dystrophy. Further, modulation of MCU activity may act as a potential pharmacological target in various conditions involving muscle loss. Abstract : In C. elegans body wall muscle, resting [Ca 2+ ]mito levels increased with age, and high‐intensity dots of mitochondria‐targeted red fluorescent Ca 2+ indicators were frequently separated from highly connected mitochondria. These processes proceeded by mitophagy, which accelerated mitochondrial fragmentation and volume loss. [Ca 2+ ]mito levels were also elevated, leading to progressive muscle wasting in a model of muscular dystrophy. Inhibition of Ca 2+ influx into mitochondria via the mitochondrial calcium uniporter alleviated mitochondrial dysfunction and improved muscle health in both aging and dystrophic models.